قياس العبء والجهد الضريبي في الاقتصاد العراقي للمدة 2004-2020 - احمد, دلمان كامل; محمد, دلگش احمد; محمد, شلير مصطفى (Sulaimani Journal for Humanities, 2022)
Taxes are an important tool for public revenues in any country, and despite the dependence of Iraqi economy on natural resources and the dominance of the oil source over the general revenues of the federal budget, taxes still set up the second source. Therefore this research tries to draw conclusions in regads to taxes or what pressure taxes can pose on society, by measuring and analyzing two important indicators which are tax burden and tax effort. The period from 2004-2020 was chosen as a time limit for the research, through which the direction of the burden and effort in Iraq could be determined. The research an important conclusion, which is that the pressure of effort and tax burden in Iraq not severe on different groups of members of society, due to the high oil revenues, which often accounted for 90 to 95% of the federal budget revenues. In addition, the backwardness at the level of tax institutions and the lack of tax awareness on individual basiscontributed significantlyto the decline in the rates of tax burden and effort during the study period.
Keywords: Public revenue; taxes; tax burden; tax effort; GDP